Prostate cancer : a multidisciplinary approach to diagnosis and management - Dicker, Adam P.; Kelly, Wm. Kevin (William Kevin); Zaorsky, Nicholas G.; Zaorsky, Nicholas G.; Trabulsi, Edouard J. (Current multidisciplinary oncology., 2015)
"With an emphasis on multidisciplinary collaboration and decision-making, this practical resource reflects the extraordinary advances in the treatment of prostate cancer during the past five years. Approximately thirty international, leading-edge investigators describe the most current evidence-based approaches to prostate cancer treatment. The book provides a comprehensive view of the entire spectrum of prostate cancer management from initial screening through novel and experimental treatments that have the potential for a major impact on practice"--Publisher's description